Without sword, (in Algeria), with the pen and the word: (Dis) indolent Enlightenment in the search of Sarmiento, “Postcolonial” (Praxis Educativa, 2022)
The present work tries to recover the existing tension between Sarmiento and the Enlightened intelligentsia of his time that leads him to make different trips in search of dialogues and “other” sources to consolidate his future vision of the state education system. Among these itineraries, there is his trip to Algeria (“Arjel”), a destination scarcely approached for its local historical and pedagogical analysis. This is how we ask ourselves if it is possible to locate this destination as a gateway to a referential framework and a metaphor for the search for interruption of power with said matrix as the only source of legitimacy. Along with this, we will also make brief references to some political and ideological debates that tried to constitute and contribute, from other positions, to the construction of a Latin American pedagogical thought from another continental identity, exteriority and laterality.
Keywords: Sarmiento; postcolonial Latin American pedagogical thought